(untitled) (INTEK : Jurnal Informatika dan Teknologi Informasi, 2025)
Optimally functioning academic services play a crucial role in supporting the operational success of a higher education institution. However, many universities still face various challenges in managing these services, such as the lack of prompt response to student complaints, suboptimal academic data management, and delays in providing solutions. To address these challenges, this study designs and develops an Academic Helpdesk application using the Agile approach. Agile was chosen because it offers flexibility, adaptability to changes, and accelerates the software development process. This application focuses on supporting academic services, including complaint handling, monitoring the status of submissions, and providing faster and more systematic solutions. Based on testing results, the application has proven to enhance service efficiency by reducing complaint handling time by up to 40% compared to traditional methods. Furthermore, surveys indicate an increase in user satisfaction among both students and academic staff, reaching 85%. These findings demonstrate that implementing the Agile method in the development of the Academic Helpdesk is an innovative and adaptive approach to improving academic services in higher education environments.